2021
DOI: 10.3390/polym13091377
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Furan-Polyesters/Graphene Nanocomposites Prepared by In Situ Polymerization

Abstract: In situ intercalative polymerization has been investigated as a strategic way to obtain poly(propylene 2,5-furandicarboxylate) (PPF) and poly(hexamethylene 2,5-furandicarboxylate) (PHF) nanocomposites with different graphene types and amounts. Graphene (G) has been dispersed in surfactant stabilized water suspensions. The loading range in composites was 0.25–0.75 wt %. For the highest composition, a different type of graphene (XT500) dispersed in 1,3 propanediol, containing a 6% of oxidized graphene and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Obviously, both graphene and silica accelerated the crystallization of PHF by acting as nucleation agents . Vannini et al also reported the preparation of PHF composites by introducing graphene with different types and amounts . An increase of around 10–20% in the storage modulus was detected in PHF composites, indicating that a better interfacial between graphene and matrix was formed through the in situ method …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Obviously, both graphene and silica accelerated the crystallization of PHF by acting as nucleation agents . Vannini et al also reported the preparation of PHF composites by introducing graphene with different types and amounts . An increase of around 10–20% in the storage modulus was detected in PHF composites, indicating that a better interfacial between graphene and matrix was formed through the in situ method …”
Section: Introductionmentioning
confidence: 99%
“…Compared to those of PEF and poly(propylene 2,5furandicarboxylate) (PPF), the lower T p and T m of PHF are considered an advantage in reducing energy consumption during melt processing. 6,11,21,26 In addition, PHF showed a comparable toughness with relatively high elongation at break of around 200%. 20 Moreover, PHF exhibited a faster crystallization rate than PEF, PPF, and poly(neopentyl glycol furandicarboxylate) (PNF).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations